Total Knee Arthroplasty in Patients with Distal Femoral Malunion: A Case Report - Paulus Ronald Hibono; Andito Wibisono (The Hip and Knee Journal, 2021)
Background: Post-traumatic arthrosis can occur subsequent to fracture of the distal femur related to residual malalignment or direct intraarticular injury. The presence of extra articular deformities either in the femur or the tibia with arthritis of the knee makes total knee arthroplasty (TKA) technically demanding. We report our initial experience on such complex knee arthroplastyCase Presentation: A 69-year-old female complained of progressive right knee pain, limited range of motion and obvious varus deformity of the right knee. She had a trauma history 13 years ago on femur side, operated and subsequent removal of implant 2 years after. Preoperative radiographs showed severe osteoarthritis on medial side and patellofemoral joint and malunion supracondylar and varus deformity. Total knee arthroplasty (TKA) was done using standard jig and equipmentConclusion: Correction could be possible to perform in majority of TKA for extraarticular deformities with good preoperative planning and templating, intraarticular bone resection and good soft tissue balancing both in flexion and extension.